2019
DOI: 10.3389/fmicb.2019.02188
|View full text |Cite
|
Sign up to set email alerts
|

The Underlying Mechanism of 3-Hydroxyphthalic Anhydride-Modified Bovine Beta-Lactoglobulin to Block Human Papillomavirus Entry Into the Host Cell

Abstract: We have previously demonstrated that 3-hydroxyphthalic anhydride (3HP)-modified bovine beta-lactoglobulin (3HP-β-LG) is highly effective in inhibiting entry of pseudovirus (PsV) of high- and low-risk human papillomavirus (HPV) into the target cell. Intravaginally applied 3HP-β-LG-containing vaginal gel could significantly inhibit HPV infection and reduce viral load in the cervical region. However, we still do not understand the underlying molecular mechanism by which 3HP-β-LG is able to inhibit HPV infection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Our previous studies have also certified that HP-OVA has no harmful or deleterious impact on the function of immune cells ( Li et al, 2010a ). Actually, anhydride-modiβed proteins, such as anhydride-modiβed bovine β-lactoglobulin, have been studied and utilized as microbicides against HIV and HPV in clinics for years, and their effectiveness and safety as drugs have been veriβed ( Neurath et al, 1996 ; Guo et al, 2016 ; Hua et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies have also certified that HP-OVA has no harmful or deleterious impact on the function of immune cells ( Li et al, 2010a ). Actually, anhydride-modiβed proteins, such as anhydride-modiβed bovine β-lactoglobulin, have been studied and utilized as microbicides against HIV and HPV in clinics for years, and their effectiveness and safety as drugs have been veriβed ( Neurath et al, 1996 ; Guo et al, 2016 ; Hua et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have reported that several kinds of viruses, including human immunodeficiency virus (HIV), human papillomavirus (HPV), respiratory syncytial virus (RSV), and novel human coronavirus MERS-CoV, can be inhibited at the viral entry step by anhydride-modified proteins ( Li et al, 2010a ; Zhao et al, 2013 ; Hua et al, 2019 ). Furthermore, one kind of anhydride-modified bovine protein, β-lactoglobulin (β-LG), was clinically applied to treat HPV infection ( Hua et al, 2019 ). Therefore, we decided to investigate whether anhydride-modified proteins could be utilized as anti-SARS-CoV-2 antivirals.…”
Section: Introductionmentioning
confidence: 99%
“…Also, HPV58-PsV entry in vitro was found to be inhibited by JB01 with an IC 50 of 0.28 µg/mL [151]. Mechanistically, the negatively charged regions on JB01 were shown to bind to the positively charged region of the HPV L1 protein, and this interaction was proposed to competitively block the binding of HPV to the receptor on the basement membrane in the vaginal mucosa (Figure 1) [151].…”
Section: Anhydride-modified Protein (Jb01)mentioning
confidence: 99%
“…Due to a lack of delivery system and high solubility of 3-hydroxyphthalic anhydride-modified bovine beta-lactoglobulin [30], existing studies can only culture cells directly in a protein-containing solution [31]. As for the in vivo application, the previous clinical application method was to use it in a gel, but it needs to be applied once every two days, which is inconvenient for patients [33]. Therefore, the hydrogel system with controlled release function in this study has great application prospects.…”
Section: Introductionmentioning
confidence: 99%